Comparative Analysis on the Improvement of Aggravate Punishment for Recidivism in Malaysia - Yichen Pan (Westscience Press, 2023)
Recidivism, the fact that individuals re-offend after being convicted of a crime, is a significant challenge faced by criminal justice systems worldwide. The study will begin by reviewing relevant literature and legal frameworks pertaining to recidivism and aggravated punishment in Malaysia. The analysis will delve into the objectives, principles, and legal provisions that guide the application of aggravated punishment for repeat offenders in the Malaysian criminal justice system. Additionally, a comparative perspective will be adopted to examine the experiences and practices of other jurisdictions that have implemented similar punitive measures for recidivism. This comparative analysis delves into the strategies employed by Malaysia for the improvement of aggravated punishment concerning recidivism within its criminal justice system. Malaysia, like many countries, has adopted measures to address but leaves several concerns on this issue. Those concerns include the range of defining recidivism unreasonably and focusing too much on crimes that violate property and the discretion of judges for sentencing them are so huge. The study evaluates Malaysia's approach to aggravated punishment for recidivism by examining the legal framework, and sentencing guidelines, and also focuses on the rights of offenders. Furthermore, it compares Malaysia's practices with those of other nations including both civil law and common law countries to identify best practices and potential areas for enhancement. By employing a comparative research methodology, the study will explore the strengths and weaknesses of the aggravated punishment approach in deterring recidivism, ensuring public safety, and promoting rehabilitation. It will critically evaluate the legal and ethical considerations associated with imposing harsher penalties on repeat offenders, including questions of proportionality, fairness, and human rights implications. Ultimately, the study strives to provide several potential ways to address those concerns for enhancing the Malaysian criminal justice system's response to recidivism, considering the principles of proportionality, and fairness in criminal justice.